The estimation of carbon storage in the seagrass meadows of Badi Island - Baharuddin, Nurazizah Pratiwi; Yaqin, Khusnul; Mashoreng, Supriadi (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
Global warming is becoming increasingly apprehensive day by day, marked by the continued increase in levels of carbon dioxide (CO2) in nature. One of the efforts made to reduce the effects of global warming is biosequestration by empowering photosynthetic organisms, one of which is seagrass beds. This study aims to measure the density and percentage of seagrass cover, biomass value, and estimate carbon storage in seagrass biomass in the form of tissue at the top (leaves and upright stems) and tissue at the bottom (roots and rhizomes), as well as estimate carbon storage in sediments. Sampling was carried out using line transect and quadrant plot methods at each station. Calculation seagrass carbon storage using the Loss of Ignition (LOI) method at the Soil Chemistry Laboratory of the Pangkep State Agricultural Polytechnic, a total of 5 species of seagrass were found, namely Enhalus accoroides, Thalassia hemprichii, Halodule uninervis, Halopila ovalis, and Cymodocea rotundata. The average seagrass carbon storage on Badi Island is 18.92 gC/m2, or 0.189 MgC/ha. The species that act as the largest contributor to carbon storage are Cymodocea rotundata, namely 35.44 gC/m2, and Halopila ovalis, which acts as the lowest contributor to carbon storage, namely 1.92 gC/m2. The average seagrass carbon storage at the bottom of the substrate was three times greater than that at the top of the substrate, namely 14.10 gC/m2 at the bottom and 4.82 gC/m2 at the top. The average carbon storage in sediments is 10.98 gC/m2, or 0.109 MgC/ha.